2022
DOI: 10.1021/acssuschemeng.2c03326
|View full text |Cite
|
Sign up to set email alerts
|

From the Design of Multifunctional Degradable Epoxy Thermosets to Their End of Life

Abstract: The development of multifunctional epoxy thermosets that meet the requirements of sustainable development by creating new macromolecular architectures, i.e., novel epoxy monomers, is a real challenge. Herein, a bis-imidazolium cycloaliphatic epoxidized room temperature ionic liquid (CEIL) was successfully synthesized at multigrams scale (1−200 g) and used as molecular brick platforms to design various networks combined to a computational approach. Thus, three epoxy networks were developed by cationic polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…Forcefield parameters were taken from the CL&Pol polarizable forcefield for ionic liquid components with OPLS-AA parameters used with polarization added for epoxy, ester, and CO 2 components . The CL&Pol forcefield has previously been shown to accurately simulate experimental properties such as density for base anions and cations used in this study, thus making it ideal to use as a base forcefield to apply. , From the applied forcefield, the density values found by our fundamental and theoretical investigation corroborate the magnitude of density experimentally obtained for a library of imidazolium-based IL monomers, including the tri- and tetra-epoxy monomers bearing the anion NTf 2 – instead of Cl – . In the current contribution, the densities predicted were 1.24 and 1.28 mg/mL for tri- and tetra-epoxy monomers. Similarly, our co-workers found 1.25 ∓ 0.05 mg/mL and 1.33 ∓ 0.06 mg mL –1 for the identical backbone monomers bearing NTF 2 – as a counterion instead of Cl – …”
Section: Theoretical Methodologysupporting
confidence: 70%
“…Forcefield parameters were taken from the CL&Pol polarizable forcefield for ionic liquid components with OPLS-AA parameters used with polarization added for epoxy, ester, and CO 2 components . The CL&Pol forcefield has previously been shown to accurately simulate experimental properties such as density for base anions and cations used in this study, thus making it ideal to use as a base forcefield to apply. , From the applied forcefield, the density values found by our fundamental and theoretical investigation corroborate the magnitude of density experimentally obtained for a library of imidazolium-based IL monomers, including the tri- and tetra-epoxy monomers bearing the anion NTf 2 – instead of Cl – . In the current contribution, the densities predicted were 1.24 and 1.28 mg/mL for tri- and tetra-epoxy monomers. Similarly, our co-workers found 1.25 ∓ 0.05 mg/mL and 1.33 ∓ 0.06 mg mL –1 for the identical backbone monomers bearing NTF 2 – as a counterion instead of Cl – …”
Section: Theoretical Methodologysupporting
confidence: 70%
“…The tan δ curve profiles indicate the total energy that the materials absorb. In recent work by our group, it was noticed that the introduction of IL monomers into a classical epoxy network significantly increased the amplitude of tan δ max . Herein, the employment of D230 yielded greater amplitudes of tan δ max , which is associated with a greater molecular mobility, meaning that the material can better absorb and dissipate energy.…”
Section: Resultsmentioning
confidence: 87%
“…This is striking due to the ratio being strongly correlated to SM performance. Our previous report on designing hybrid networks showed that the integration of an IL monomer into a classical epoxy network can increase the G g / G r ratio from 31 to 351, improving the SM performance as a function of IL monomer proportion …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations